2020
DOI: 10.23925/2594-3871.2020v29i1p176-200
|View full text |Cite
|
Sign up to set email alerts
|

Autores de Violência Sexual e o Teste de Rorschach: Revisão da Literatura

Abstract: O objetivo deste estudo foi realizar uma revisão da literatura de publicações que investigam a personalidade do autor de violência sexual por meio do teste de Rorschach. Realizou-se uma busca bibliográfica nas bases de dados PubMed, Psycnet, Web of Science, PePSIC e SciELO, com descritores: “Sex Offender”, “Pedophile”, “Sex Offenses”, “Sexual Molester”, “Sexual Violence” e “Rapist”, combinados com Rorschach. A busca foi limitada aos artigos publicados nos idiomas inglês, espanhol e português, dos últimos quinz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…that all these impairments corroborate the predisposition for the SO not only to commit the sexual crime but also to repeat this behavior (Zilki et al, 2020).…”
supporting
confidence: 58%
“…that all these impairments corroborate the predisposition for the SO not only to commit the sexual crime but also to repeat this behavior (Zilki et al, 2020).…”
supporting
confidence: 58%
“…The analysis showed that the total group presents compromised intellectual performance: Complexity (t = -5.84; p < 0.001), MC (t = -7.65; p < 0.001). In a literature review study on PSVs against children and adolescents, who were evaluated using the Rorschach method, Zilki et al (2020) found evidence that these individuals have some type of deterioration of the neuropsychological and intellectual functions, that impair the way they engage and process the surrounding information. In addition, the co-occurrence of Antisocial Personality Disorder and paraphilia would be associated with poor cognitive performance (Azizian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This schema makes up the domain of distancing and rejection, which encompasses individuals who are characterized by the inability to create stable bonds with others, with a perception that their individual needs for security, protection, stability, love and respect will not be met. It can be assumed that, in these individuals, the personal difficulty of creating bonds projects on children the greatest potential for acceptance and recognition, given that, according to the literature (Finkelhor, 1984;Howitt, 2009;Chudzik, & Réveillère, 2013;Scortegagna, & Amparo, 2013;Zilki, Aguiar, Perissinotto, & Resende, 2020), a large portion of the sexual victimizers of children are immature, emotional, and assume that these individuals have emotional needs that are met in the context of their relationships with the children.…”
Section: Discussionmentioning
confidence: 99%